OUTCOMES OF THE LONG-TERM ADMINISTRATION OF MACROLIDE ANTIBIOTICS IN CHILDREN WITH BRONCHIECTASES: FREQUENTLY ASKED QUESTIONS - Natal’ya B. Lazareva; Evgeniya V. Chikh; Ekaterina V. Rebrova (Вопросы современной педиатрии, 2018)
The article discusses issues related to the long-term administration of macrolide antibiotics for a bronchoectatic disorder of the pulmonary system in children. The relevant information about the results of long-term intake of macrolides in adults and children, the effective dose titration, possible toxic effects of therapy, including the development of cardiotoxic effect and ways to prevent it, has been enlightened in detail. It has been noted that a limited number of clinical studies involving children determine the need for studying the possibility to extrapolate adult treatment.